J R Bowen, a new anthropology of Islam - Solomon, H. (University of the Free State, 2014)
Abstract not available
J. R. Bowen, 2012, A new anthropology of Islam Cambridge: Cambridge University Press, ISBN 978 0 521 52978 5.
Keywords: Bowen, J. R.; A new anthropology of Islam; Social anthropology; Book review